2005
DOI: 10.1002/jemt.20191
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent human lung macrophages analyzed by spectral confocal laser scanning microscopy and multispectral cytometry

Abstract: Numerous highly fluorescent macrophages (MU), designated ''smoker cells,'' exist in the lungs of smokers and subjects who have quit smoking within 5 years. The brightly fluorescent MU, however, are not present in the lungs of never smokers. Some investigators have speculated that the intense fluorescence of the MU is due to smoke-induced changes in the autofluorescence of naturally occurring (i.e., endogenous) compounds (e.g., NADP). In contrast, other researchers have theorized that the fluorescence is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The alveolar entrances and alveolar ducts of smokers were usually filled with highly fluorescent cells, the movements of which could be clearly observed (see online video). Bronchoalveolar lavage analysis from smokers using fluorescence and conventional microscopy confirmed that these fluorescent cells correspond exclusively to alveolar macrophages [15].…”
Section: Alveolar Imaging Of Active Smokersmentioning
confidence: 75%
“…The alveolar entrances and alveolar ducts of smokers were usually filled with highly fluorescent cells, the movements of which could be clearly observed (see online video). Bronchoalveolar lavage analysis from smokers using fluorescence and conventional microscopy confirmed that these fluorescent cells correspond exclusively to alveolar macrophages [15].…”
Section: Alveolar Imaging Of Active Smokersmentioning
confidence: 75%
“…Studies of laser-generated optical sections have shown that the greatest contributors are polycyclic aromatic hydrocarbons (see Discussion in ref. 17).…”
Section: Discussionmentioning
confidence: 99%
“…Notable is that the lung of a long-term smoker contains a large and unique population of ''pigmented'' MU that is readily seen in conventional white-light examinations of stained wax block sections [27,28]. Also, pigmented MU display a high level of fluorescence that is associated with the ingestion of tobacco smoke particulates (''tar'') [27][28][29]. The florescent MU, designated as ''smoker cells'' are not present in the lungs of non-smokers, including subjects who have been exposed to high levels of smoke and diverse airborne particulates in different environmental and occupational settings [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary clinically defined events of smoke-associated inflammation is the influx of macrophages (MU) [2][3][4][5][6][7][8]10]. Notable is that the lung of a long-term smoker contains a large and unique population of ''pigmented'' MU that is readily seen in conventional white-light examinations of stained wax block sections [27,28]. Also, pigmented MU display a high level of fluorescence that is associated with the ingestion of tobacco smoke particulates (''tar'') [27][28][29].…”
Section: Introductionmentioning
confidence: 99%